Three merchants of Bombay : business pioneers of the nineteenth century / introduction by Gurcharan Das - Subramanian, Lakshmi (Gurgaon, 2012)
Three Merchants of Bombay is the story of three intrepid merchants who traded out of Bombay in the nineteenth century?Tarwady Arjunjee, Jamsetjee Jeejeebhoy and Premchand Roychand?founding pioneering business empires based on trade in cotton and opium. Set against the backdrop of global and local economies undergoing rapid and unforeseen change, these stories stand as a microcosm for the history of indigenous capitalism in western India. In this succinct and lucid account, Lakshmi Subramanian traces that history and locates it in the greater narrative of the economic development of India, South Asia and the world.